Foliar Application of Iron Oxide Nanoparticles Enhances Morphophysiological Characteristics and Yield Performance of Capsicum annuum L. in a Controlled Environment - Sarobo, Zulaikha; Dzahir, Noorafizah; Jalal, Mohd Azlan; Rosli, Mohamad Azzuan; Abd Aziz, Nazrin; Ridzuan, Raihana; Magaji, Usman; Johan, Mohd Rafie; Suppiah, Durga Devi; Ab. Rani, Norlia (Journal of Advanced Research Design, 2025)
Iron (Fe) is an essential micronutrient that plays a vital role in several plant physiological processes. Nevertheless, iron deficiency remains a significant challenge in chili plants, particularly affecting their fruit production. Therefore this study aimed to characterize the physicochemical of iron oxide nanoparticles (IONPs) and investigate the effects of foliar-applied IONPs on the growth, physiological responses, and yield parameters of Capsicum annuum. The physicochemical characteristics of IONPs were analyzed using a High-Resolution Transmission Electron Microscope and scanning electron microscopy with energy dispersive X-ray spectroscopy. Six IONPs concentrations (0, 50, 100, 200, 400, and 800 mg/L) were applied through foliar spray on chili plants during four critical growth stages: vegetative growth, flowering, fruit development, and maturity. The findings revealed the spherical, uniform surface structures with an average size of 12–20 nm and 58.2% of iron composition. On the other hand, the field evaluation demonstrated that foliar application of IONPs at concentrations between 200 mg/L significantly enhanced plant height and photosynthesis activity compared to control treatment. In terms of yield, 400 mg/L IONPs resulted in the highest fruit yield compared to control treatments. This research establishes the effectiveness of IONPs as a growth promoter and yield enhancer in chili cultivation, with optimal concentrations identified for commercial application. Future research should focus on long-term effects and environmental impacts to develop comprehensive application guidelines for sustainable agricultural practices.